Implikatur Percakapan Pada Ungkapan Pemberlakuan Kurikulum 2013 Di SMK N 8 Surakarta - PRAYOGO, HARI; , Dra. Atiqa Sabardila, M. Hum (2016)
HARI PRAYOGO / A310120120. CONVERSATIONAL IMPLICATURE ON THE IMPLEMENTATION OF CURRICULUM 2013 EXPRESSION IN SMK N 8 SURAKARTA. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. June, 2016. This study aimed to describe the shape and purpose of conversational implicature on the implementation of Curriculum 2013 expression in SMK N 8 Surakarta. Penelititan type is qualitative research using the method description. Sources of data in this study is that teachers do conversations related to the implementation of Curriculum 2013. The research data that is an expression of the implementation of the Curriculum 2013 at SMK N 8 Surakarta. Data collection techniques using methods see that followed up with a technique noted. Data were analyzed using the technique sorting determinants pilah pragmatic elements and using advanced engineering techniques that equate appeal circuited by means of the equation: the standard equations or pembaku. The results of the first study is a form of conversational implicature on the implementation of Curriculum 2013 expression in SMK N 8 Surakarta can be classified into eight forms. (1)Implicature shape that has the intent to tell the implementation of Curriculum 2013, twelve speech. (2)Forms implicatures have complained constraints mean Curriculum 2013 seven utterances. (3)Implicature shape that has the intent to question the process of curriculum in 2013 as many as five utterances. (4)Forms implicatures have satirical intent curriculum implementation in 2013 of four speech. (5)Implicature shape which has the sole alleged readiness of students for three utterances. (6)Implicature shape which has the sole doubts curriculum implementation in 2013 of two utterances. (7)Implicatures has the sole form of sadness to evaluate students as much as one speech. (8)Implicatures has the sole form of pleading of material changes by one speech. The results of the second study is the intent of conversational implicature on the implementation of Curriculum 2013 expression in SMK N 8 Surakarta can be classified into two purposes. (1)The purpose of the literal speech acts as much as thirty four speech. (2) Mean literal speech acts not as much as a speech. Keywords: Implicatures, Curriculum 2013, Speech, SMK N 8 Surakarta.